Brand Image Analysis as Examined Through Perceived Exhibition Atmosphere and Art Involvement With Visitor Satisfaction as an Intervening Variable (An Empirical Study at Museum MACAN, Jakarta) - Popy Francisca Waraswasti; Supriadi Thalib; Iha Haryani Hatta; Yuli Ardianto (Greenation Research & Yayasan Global Resarch National, 2026)
This study examines the influence of Perceived Exhibition Atmosphere and Art Involvement on Brand Image, with Visitor Satisfaction as an intervening variable among visitors to Museum MACAN Jakarta. The study is motivated by the growing popularity of contemporary art museums in Indonesia, which has not always been accompanied by strong visitor satisfaction and a sustainable brand image. A preliminary survey revealed a predominance of neutral responses across key variables, indicating perceptual ambiguity as well as practical and academic gaps in the Indonesian museum context. A quantitative approach with a cross-sectional design was employed. Data were collected through questionnaires from 200 Museum MACAN visitors aged 17–60 using purposive sampling. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine causal relationships and the mediating role of visitor satisfaction. The results demonstrate that Perceived Exhibition Atmosphere and Art Involvement have a positive and significant effect on Visitor Satisfaction and Brand Image. Furthermore, Visitor Satisfaction has a positive and significant effect on Brand Image and mediates the relationship between the antecedent variables and brand image. These findings highlight that visitor satisfaction plays a critical role in translating exhibition experiences and artistic engagement into a positive and sustainable museum brand image.